Informal finance for survivalist enterprise development in South Africa: A case study of Soshanguve Township - Mashigo, Mariann Polly (School for Basic Sciences, Vaal Triangle Campus, North-West University, 2015)
The majority of South Africans are trapped in poverty and high unemployment levels. Some, particularly the poor, resort to operating survivalist enterprises to cater for day-to-day expenses or meet basic needs. The underlying problem confronting many survivalist enterprises is lack of finance to develop and sustain their enterprises which is associated with collateral constraints. As a result, survivalist enterprises use informal sources of finance as channels to access such finance. The objective of this article is to determine how informal finance can mitigate this problem and propose strategic finance principles that can be used to improve access to finance by survivalist enterprises. The research adopted a case study approach based on informal finance and how it is used as an instrument for developing survivalist enterprises in the Soshanguve township situated in the Gauteng Province in South Africa. A sampling technique was employed to conduct interviews with survivalist enterprises which were randomly selected. The research findings reveal that informal finance appears to be successful through its traditional norms and customs embedded in the informal financial arrangements which mitigate collateral problems and improve access to finance by survivalist enterprises. Based on these findings, recommendations were therefore formulated based on informal finance which can be used as the first point of reference for developing survivalist enterprises in South Africa.
Keywords: Informal Finance; Credit; Survivalist Enterprises; Collateral; Financial Institutions